Dampak Self Efficacy Terhadap Work Stress - Aprilyani, Ratnasartika (Jurnal Manajemen & Bisnis Digital, 2022)
Abstract: This research aims to determine the influence of self-efficacy on work stress. Distance learning carried out by lecturers and students has resulted in changes to the learning system process. The demand to adapt to changes in the learning system and the demand to master technology in order to be able to run a distance learning system are situations that can put lecturers in work situations that cause them to experience work stress. There are several factors that influence work stress, such as how to cope with stress, psychological resilience, emotional intelligence, self-efficacy, social support and adversity quotient. This research is included in quantitative research. The subjects in this research were 83 lecturers from universities in the Jakarta area. The sampling method uses a purposive technique. The data collection tools used were self-efficacy and work stress scales. This research uses linear regression analysis techniques to determine the influence of independent and independent variables. Data processing using the SPSS version 25.0 program. Based on the results of the multiple regression analysis, it was concluded that there was an influence between self-efficacy and work stress..   Key words: Self  efficacy,  Work  stress,  Lecturer,  Online Learning.   Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh self efficacy terhadap work stress. Pembelajaran jarak jauh yang dilakukan oleh dosen dan mahasiswa mengakibatkan proses sistem pembelajaran mengalami perubahan. Tuntutan beradaptasi terhadap perubahan sistem pembelajaran serta tuntutan untuk menguasai teknologi agar dapat menjalankan sistem pembelajaran jarak jauh merupakan situasi yang dapat membuat dosen masuk pada situasi kerja yang membuat ia mengalami work stress. Ada beberapa faktor yang mempengaruhi stress kerja seperti cara coping stress, ketahanan psikologi, kecerdasan emosional, self efficacy, dukungan sosial dan adversity quotient. Penelitian ini termasuk pada penelitian kuantitatif. Subyek dalam penelitian ini sebanvak 83 orang dosen yang berasal dari Universitas di wilayah Jakarta. Metode pengambilan sampel menggunakan teknik purposive. Alat pengumpul data yang digunakan berupa skala self efficacy dan work stress. Penelitian ini menggunakan teknik analisis regresi linear untuk mengetahui pengaruh dari variabel bebas dan independen. Pengolahan data dengan menggunakan program SPSS versi 25.0. Berdasarkan hasil analisis regresi ganda diperoleh kesimpulan terdapat pengaruh antara self efficacy terhadap work stress.   Kata kunci: Self efficacy, Work stress, Dosen, Pembelajaran Jarak Jauh.